2003
DOI: 10.4049/jimmunol.171.3.1493
|View full text |Cite
|
Sign up to set email alerts
|

Human Mast Cell β-Tryptase Is a Gelatinase

Abstract: Remodeling of extracellular matrix is an important component in a variety of inflammatory disorders as well as in normal physiological processes such as wound healing and angiogenesis. Previous investigations have identified the various matrix metalloproteases, e.g., gelatinases A and B, as key players in the degradation of extracellular matrix under such conditions. Here we show that an additional enzyme, human mast cell β-tryptase, has potent gelatin-degrading properties, indicating a potential contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 46 publications
3
40
0
3
Order By: Relevance
“…Mast cells are reported to specifically influence granulation tissue organization during wound repair [5]. All these findings support the fact that degranulation promotes fibrosis but at the same time other products of degranulation such as tryptase also play a role in the degradation of connective tissue [11]. Thus, the increase in collagen detected after tryptase treatment must reflect an increase in the net biosynthetic rate of type I collagen.…”
Section: Discussionsupporting
confidence: 70%
“…Mast cells are reported to specifically influence granulation tissue organization during wound repair [5]. All these findings support the fact that degranulation promotes fibrosis but at the same time other products of degranulation such as tryptase also play a role in the degradation of connective tissue [11]. Thus, the increase in collagen detected after tryptase treatment must reflect an increase in the net biosynthetic rate of type I collagen.…”
Section: Discussionsupporting
confidence: 70%
“…Blair et al have demonstrated that direct addition of tryptase to microvascular endothelial cells cultured on Matrigel caused a pronounced increase of capillary growth, which was suppressed by specific tryptase inhibitors, and directly induced endothelial cell proliferation in a dose-dependent fashion (10). Tryptase is involved in tissue remodelling and it may also act indirectly on tissue neovascularization by releasing latent angiogenetic factors bound to the extracellular matrix (27). Tryptase is an agonist of the proteinase-activated receptor-2 (PAR-2) in vascular endothelial cells and breast cancer cells (28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid mediators such as LTC4, as well as certain cytokines such as IL-4, TNF-␣, and TGF-␤ also favor the growth of fibroblasts (69,70). Conversely, mast cell proteases such as tryptase were also found to have potent proteolytic activity toward denatured collagen or gelatin (71). Similarly, mast cell chymase has been described to activate matrix metalloproteinases 2 and 9, which also degrade denatured collagen, either by activating their proform or by degrading their natural inhibitor protein tissue inhibitor of metalloproteinase (72,73).…”
Section: Discussionmentioning
confidence: 99%